Analysis of Local Government Implementation Report Model (LPPD) in North Bolaang Mongondow Regency, North Sulawesi Province - Siske Anani; Imam Mashudi; Dini Ariyasanti (Journal La Sociale, 2020)
This study raised the title of the Analysis of Local Government Implementation Report (LPPD) in Bolaang Mongondow Utara Regency, North Sulawesi Province. The data collection technique was done by interviewing and literature study. The data analysis technique used is the Miles and Huberman model, namely data analysis which is carried out directly and continuously until it is complete, so that the data is saturated. Based on the results of the data research and analysis process carried out, it can be explained that in Article 16 of Government Regulation Number 6 of 2009 which is the implementation of Article 6 paragraph (3) of Law Number 32 of 2004 concerning Guidelines for the Evaluation of Regional Government Administration, it is stated that the source of information The main role in implementing the Implications of the Performance Evaluation of Regional Government Administration (EKPPD) is the Regional Government Implementation Report (LPPD). The LPPD itself, as stated in Law Number 32 Year 2005, states that regional heads are required to submit a Regional Government Administration Report (LPPD) to the central government. The scope of the LPPD is divided into matters of decentralization, general duties, and assistance tasks. This is stated in article 2 PP No. 3 of 2007 which contains the LPPD to the government, information on the LPPD to the public, reports on the accountability of the Regional Head to the Regional People's Representative Council (DPRD).